2011
DOI: 10.1007/s10620-011-1881-x
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Dextran Sodium Sulfate-Induced Colitis Can Differ Between Dextran Sodium Sulfate Preparations of the Same Molecular Weight Range

Abstract: The severity of colitis can differ between similar DSS preparations of the same molecular weight range. This difference in colitogenic properties may be affected by the total sulfur content of each DSS preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…On the other hand, our data suggest that MT deficiency results in disease exacerbation in a mouse model of DSS-induced colitis, and that MTs play a protective role in the development of intestinal inflammation. While considering these results, we noted differences in the manufacture of DSS and vivarium in these studies, and it has been reported that these factors can lead to differences in the severity of DSS-induced colitis (34,35).…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, our data suggest that MT deficiency results in disease exacerbation in a mouse model of DSS-induced colitis, and that MTs play a protective role in the development of intestinal inflammation. While considering these results, we noted differences in the manufacture of DSS and vivarium in these studies, and it has been reported that these factors can lead to differences in the severity of DSS-induced colitis (34,35).…”
Section: Discussionmentioning
confidence: 67%
“…14 Figure 1 displays the acute disease activity index for different experimental groups. A validated index (1 indicating no disease; 4 indicating the most severe disease) of average scores based on the combination of clinical symptoms (body weight, diarrhea, fecal occult blood/prolapse and colon length) was constructed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a recent investigation indicated that the severity of colitis can differ between similar DSS preparations of the same molecular weight range. 14 This difference in colitogenic properties may be affected by the total sulfur content of each DSS preparation. The DSS used in the present investigation was reported to cause the most severe disease and weight loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations